THE LOCAL'S LABOR MARKET: AN ANALYSIS OF CERAMIC PRODUCTION IN SANTA GERTRUDES/SP - FUINI, Lucas Labigalini (UFPR, 2008)
Under the perspective that all productive clusters is related a respective local labor market, the author analyze, in this paper, the principal characteristics of labor market associated with Santa Gertrudes/ Sao Paulo region territoriality of manufacturing pavement ceramic. In the context of deep changes in manufacture activity and labor world that drive for new special forms of economic relations, the importance of local labor market notion behind of actual Little and Medium territorialized industries clusters valorization - named APL (Local Productive Arrangements) -are examined in this text, considering it promotes potential of competitiveness and territorial development.  Considering these estimated, the main characteristics of market of work inherent to the territoriality of Santa Gertrudes’ ceramic coating industry will be analyzed.